Gestational Diabetes Mellitus and Dyslipidemia in HIV-Infected Pregnant Women Receiving PIs Based HAART - Natthawut Wetchittichareon; Suvanna Asavapiriyanont (The Royal Thai College of Obstetricians and Gynaecologists, 2013)
Objectives: To evaluate the incidence of gestational diabetes mellitus (GDM), altered lipid metabolism and birth weight in human immunodeficiency virus (HIV) infected pregnant women receiving protease inhibitor (PIs) based highly active antiretroviral therapy (HAART).Materials and Methods: A cross-sectional descriptive study of 109 HIV-infected pregnant women receiving PI-based HAART to prevent vertical viral transmission from Rajavithi and Nopparatrachathani Hospital was conducted from October 2010 to July 2012. A 100-gm oral glucose tolerance test was performed in women with abnormal 50-gm glucose challenge test during 2nd to 3rd trimester and lipid profile was measured after the 4th week of treatment. Statistics such as number and percentage were used for descriptive data. Odds ratio (OR) with 95% confidence interval (CI), Chi-square, t-test and paired t-test were used for comparison with significance at p-value < 0.05.Results:The patients' mean age was 28.9 years, most (79.8%) were naïve for HAART before pregnancy. The incidence of GDM was 7.3%. There was an increase in post treatment level of total cholesterol (TC) and triglyceride (TG) at 18.9 mg/dL (95%CI, 9.5-28.4) and 97.2 mg/dL (95%CI, 70.9-123.3), respectively. The incidence of low birth weight was 17.4%. Conclusion: Use of PI-based HAART in pregnant women was associated with increased GDM and altered lipid metabolism.